Generator Voltage Droop and Voltage - Reactive States of Transmission Network - Ivanović, Milan V; Popović, Dragan P.; Stojić, Đorđe M.; Veinović, Slavko; Milinković, Milan; Arnautović, Dušan; Minić, Saša (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
This paper examines the impact of generator voltage droop to the voltage-reactive states of transmission networks. First, voltage droop definition is given, as well as its measurement procedure and setting. Models of incorporating generator voltage droop into an analysis of static and dynamic states are given. These analyses are incorporated into appropriate computer programs, developed at the Institute "Nikola Tesla", for the static and dynamic security analyses of electrical power systems. The final chapter presents some typical examples of practical applications of static security analyses. The Serbian power system, together with neighbouring power systems has been considered. Special attention has been paid to quantifying the influence of generator voltage droop to post-dynamic quasi-stationary states